The European Union's response to the coronavirus emergency: an early assessment - Tobias Tesche (London School of Economics and Political Science (LSE), European Institute, 2020)
This article provides an assessment of the EU institutions' response to the coronavirus pandemic. It contends that it followed the new intergovernmental tendency to empower de novo bodies like the European Stability Mechanism, the European Investment Bank and the European Central Bank. The European Central Bank's early and unconstrained action structured European politics. Its pandemic emergency purchase programme ensured that euro area member states were able to maintain market access and lowered the financial attractiveness of the subsequently created instruments to tackle the corona crisis. The European Commission was relegated to the role of 'cheerleader of European solidarity'. It partially redeemed itself by creating a new temporary loan-based instrument to support national short-term work schemes and by proposing a large-scale recovery instrument termed 'Next Generation EU'.
Keywords: 330; Coronavirus crisis; pandemic emergency politics; COVID-19; euro area; EU